x x y = (13 i + 4 j - 9 k) x (- i + 7 j - 4 k)
Distribute the cross product:
x x y = 13*(-1) (i x i) + 4*(-1) (j x i) + (-9)*(-1) (k x i)
........... + 13*7 (i x j) + 4*7 (j x j) + (-9)*7 (k x j)
........... + 13*(-4) (i x k) + 4*(-4) (j x k) + (-9)*(-4) (k x k)
x x y = -13 (i x i) - 4 (j x i) + 9 (k x i)
........... + 91 (i x j) + 28 (j x j) - 63 (k x j)
........... - 52 (i x k) - 16 (j x k) + 36 (k x k)
By definition of the cross product, we have
i x i = j x j = k x k = 0
i x j = k
j x k = i
k x i = j
and for any two vectors x and y, the product is anti-symmetric:
x x y = -(y x x)
This makes the products on the "diagonal" vanish, and we can condense terms using the anti-symmetry property:
x x y = (4 + 91) (i x j) + (9 + 52) (k x i) + (63 - 16) (j x k)
x x y = 95 k + 61 j + 47 i
x x y = 47 i + 61 j + 95 k